Concept of Food Consumption in Ayurveda: A Review Article - Yadav, Ashok (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda is a comprehensive system of natural health care that has its origins in the Vedas. Because it is a different aspect of life, it is not only a treatment system, but also an ideal way of life to achieve a healthy life. Ayurveda focuses on various rules and regulations. Helps improve health and improve lifespan. The Upanishads said that the purity of food helps to purify the inner self and thus the mind and intellect. Aahar is the life of living beings. Acharya defines Aahar in detail and explains how to consume Aahar for a long and healthy life. Ahar is the first and most important factor for Swasthai Savasti Laksanam. If the correct rules of Ahar are not followed, the body will lead to Rogaavasta. Aahara plays an important role in health and disease states. Therefore, it is very important to know that the concept of Aharvidhi is related to Ayurveda and the present.